A new flavonoid from Ophiopogon confertifolius - Vinh Hue, Nguyen Thi; Thuan, Nguyen Duy; Thong, Nguyen Trong; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
From the methanolic extract of the roots of Ophiopogon confertifolius N. Tanaka (Convallariaceae) a new flavonoid named ophiofolius A (1) and two known compounds (2, 3) were isolated. Their structures were elucidated as 6,8-dimethyl-4’methoxy-5,7,3’,5’-tetrahydroxyflavanone (1), 6,8-dimethyl-3’,4’-dimethoxy-5,7,5’-trihydroxyflavanone (2), and 6-methoxy-5,7-dihydroxyflavanone (3) by the spectroscopic evidences (1D NMR, 2D NMR, ESI-MS)